Effectiveness of Participatory Education on Knowledge, Attitudes, and Malaria Prevention Practices in Endemic Communities in Indonesia: A Quasi-Experimental Study - Kismiyati, Kismiyati; Utami, Theresia Febriana Christi Tyas; Nasrah, Nasrah (Chakra Brahmanda Lentera Institute, 2026)
Background: Malaria remains a major public health problem in endemic areas of Papua, Indonesia, contributing substantially to morbidity and hindering community productivity. Effective, sustainable, and community-based prevention strategies are urgently needed to reduce transmission and improve preventive behaviors. This study aimed to assess the effectiveness of participatory education compared with conventional leaflet-based education in improving knowledge, attitudes, and malaria prevention practices among community members in an endemic area. Methods: A quasi-experimental study with a control group design was conducted involving 220 community members. Participants were assigned to an intervention group that received participatory malaria prevention education and a control group that received educational leaflets with minimal explanation. A structured Knowledge, Attitude, and Practice (KAP) questionnaire was administered before and after the intervention to measure changes in malaria-related knowledge, attitudes, and preventive practices. Data were analyzed using comparative statistical tests and paired t-tests to determine differences within and between groups. Results: The findings demonstrated a statistically significant increase in knowledge and malaria prevention practices in the intervention group (p < 0.001). In contrast, the control group showed a modest but significant improvement in knowledge (p = 0.006) and no significant change in prevention practices (p = 0.377). Neither group experienced a statistically significant change in attitudes toward malaria prevention (p > 0.05). Conclusion: Participatory education is more effective than conventional leaflet-based education in improving malaria-related knowledge and preventive practices. However, changing attitudes may require more intensive and sustained interventions. Integrating participatory approaches into routine public health programs is recommended to strengthen malaria prevention efforts in endemic community.